Exhaled Breath Analysis for the Diagnosis and Assessment of Endoluminal Gastrointestinal Diseases. Issue 1 (January 2015) - Markar, Sheraz R.; Wiggins, Tom; Kumar, Sacheen; Hanna, George B.
<x xml:space="preserve">Abstract</x> Investigation of gastrointestinal diseases is often invasive to the patient and costly. Exhaled breath analysis of volatile organic compounds (VOCs) may provide a noninvasive diagnostic tool to allow the assessment and stratification of risk. The aim of this review was to evaluate the current role of VOC breath analysis in the diagnosis and assessment of endoluminal gastrointestinal disease. Medline, Embase, Cochrane, trial registries, conference proceedings, and reference lists were searched for relevant diagnostic studies. Gastrointestinal diseases studied included inflammatory bowel disease (IBD), celiac disease, and colorectal and gastroesophageal cancer. Eleven studies comprising 934 patients were included. IBD was associated with an increase in breath alkanes compared with controls, and the degree of increase was correlated with disease activity in some studies. Colorectal cancer could be distinguished from controls on the basis of VOC profiling; however, the metabolites analyzed varied between studies preventing the generation of a reproducible diagnostic model. In isolated cohort studies, significant differences in the VOC profiles from exhaled breath of patients with gastroesophageal cancer were observed, suggesting that this may have a future role as a noninvasive diagnostic test. Assessment of the cumulative level of surrogate validity for disease-specific breath analysis suggested that the best evidence is for esophagogastric cancer followed by colorectal cancer and IBD. Exhaled breath analysis of VOCs does provide a potential noninvasive tool to determine risk of gastrointestinal disease. Future areas for research include: standardizing breath tests and improving mechanistic understanding of the VOCs associated with specific gastrointestinal disease states in large multicenter population studies.